Damage associated molecular patterns and neutrophil extracellular traps in acute pancreatitis - Zhou, Xiaoying; Jin, Shengchun; Pan, Jingyi; Lin, Qingyi; Yang, Shaopeng; Ambe, Peter C.; Basharat, Zarrin; Zimmer, Vincent; Wang, Wei; Hong, Wandong (Frontiers in Cellular and Infection Microbiology, 2022)
Previous researches have emphasized a trypsin-centered theory of acute pancreatitis (AP) for more than a century. With additional studies into the pathogenesis of AP, new mechanisms have been explored. Among them, the role of immune response bears great importance. Pro-inflammatory substances, especially damage-associated molecular patterns (DAMPs), play an essential role in activating, signaling, and steering inflammation. Meanwhile, activated neutrophils attach great importance to the immune defense by forming neutrophil extracellular traps (NETs), which cause ductal obstruction, premature trypsinogen activation, and modulate inflammation. In this review, we discuss the latest advances in understanding the pathological role of DAMPs and NETs in AP and shed light on the flexible crosstalk between these vital inflammatory mediators. We, then highlight the potentially promising treatment for AP targeting DAMPs and NETs, with a focus on novel insights into the mechanism, diagnosis, and management of AP.